The Effect of Financial Distress on Consumer Non-Cyclical Stock Prices on the Indonesia Stock Exchange In 2019-2021 - Anak Agung Pradnya Satya Nugraha; Made Gede Wirakusuma (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the effect of financial distress on the stock prices of manufacturing companies in the consumer non-cyclical sector on the Indonesia Stock Exchange in 2019-2021 using the Altman Z-score model. The number of samples used is 48 companies with non-probability sampling method. Data collection was carried out using a purposive sampling technique with criteria, namely main board consumer non-cyclical sector companies that were actively traded on the IDX in a row during the 2019-2021 period. The acquired data was then subjected to simple linear regression analysis. The study's findings demonstrate that the Z-score status significantly positively affects stock prices, there are also differences in the Z-score status at different times, namely between before and during the COVID-19 pandemic. The implication of this study is the existence of financial distress by using the Altman Z-score analysis as an indicator for investors to consider before investing in a company.